2013
DOI: 10.3233/nre-130942
|View full text |Cite
|
Sign up to set email alerts
|

Excitability of spinal neural function during several motor imagery tasks involving isometric opponens pollicis activity

Abstract: BACKGROUND: It is unclear whether mental simulation without actual muscle contraction associated with actual motion can increase the excitability of the spinal neural function. OBJECTIVE: To determine the best method for mental simulation without actual muscle contraction, we analyzed the F-wave of thenar muscles after stimulating the median nerve by motor imagery whilst holding the sensor of a pinch meter between the thumb and index finger and without holding the sensor. METHODS: Healthy volunteers (n = 11; m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 14 publications
1
30
0
Order By: Relevance
“…A significant increase of the spinal motor neuron excitability was observed during MI [16,17]. Our previous study also demonstrated a significant increase of the spinal motor neurons during MI of isometric thenar muscle activity at 50% maximal voluntary contraction (MVC) [18]. Conversely, previous studies demonstrated that excitability of spinal motor neurons is not changed during MI [14,19,20].…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…A significant increase of the spinal motor neuron excitability was observed during MI [16,17]. Our previous study also demonstrated a significant increase of the spinal motor neurons during MI of isometric thenar muscle activity at 50% maximal voluntary contraction (MVC) [18]. Conversely, previous studies demonstrated that excitability of spinal motor neurons is not changed during MI [14,19,20].…”
Section: Introductionmentioning
confidence: 81%
“…Our research group previously reported that the excitability of spinal motor neurons was significantly increased during MI of isometric thenar muscle activity at 50% MVC [18]. In actual movement, the excitability of spinal motor neurons was increased linearly with muscle contraction strength [22].…”
Section: The Excitability Of Spinal Motor Neurons During MI At Differmentioning
confidence: 89%
See 1 more Smart Citation
“…At the end of chapter, we discuss about how apply MI to neurorehabilitation using brain-machine interface (BMI). We previously reported that when the subject performed MI of isomeric thenar muscle activity at 50% MVC, the spinal motor neuron excitability was significantly increased than at rest [20]. In actual motion, Suzuki et al [27] reported the spinal motor neuron excitability was increased linearly with muscle contraction strength.…”
Section: Introductionmentioning
confidence: 96%
“…Oishi et al [19] also reported that there was decline of H-reflex amplitude during MI of speed skating. Our laboratory previously investigated the spinal motor neuron excitability during MI of isometric thenar muscle activity at 50% maximal voluntary contraction (MVC) for 1 min using the F-wave [20]. The F-wave is a compound action potential resulting from re-excitation ("backfiring") of an antidromic impulse following distal electrical stimulation of motor nerve fibers at the anterior horn cells [21][22][23].…”
Section: Introductionmentioning
confidence: 99%